The impact of IFRS adoption on foreign direct investment in CIS - Sherkulov Sanjar; A K M Kamrul Hasan; Indira Khajieva; Gulhayo Nusratova; Feruza Yodgorova (Financial Internet Quarterly, 2022)
Exploring the relationship between International Financial Reporting Standards (IFRS) and Foreign Direct Investment (FDI) inflows is the main objective of this paper. Although IFRS is identified as a determinant of FDI, a few studies have examined the impact of IFRS on FDI inflows, and it is unexplored as to whether IFRS impacts CIS countries. This paper covers ten (10) IFRS adopted CIS countries from 2000 to 2019 using Ordinary Least Square (OLS) and bias-corrected Least Square Dummy Variable (LSDVC). OLS estimator shows that IFRS positively impacts FDI inflows. However, according to the results of LSDVC, there is a negative relationship between IFRS adoption and FDI inflows. Generally, in developing countries implementing IFRS would lead to FDI enhancement. The negative relationship between IFRS adoption and FDI inflows in CIS countries shows that IFRS is not an essential factor of FDI inflows.
Keywords: M41; M48; F35; EO2; 330; IFRS; FDI; CIS countries